A Synthesis of Applied Nanotechnology to Electronics - Kremer, Ingridi dos Santos (2020)
Nanotechnology is the control of small-scale matter as atomic and molecular. She works in the development of materials and components for various areas of knowledge such as electronics, catalysis, medicine and other areas. Being one of the most benefited electronics. The application of nanotechnology in electronics has brought new concepts to the area allowing to minimize electronic devices, use of semiconductors, conductors, diodes, transistors and other components built in small scales, it can be observed that they are presented smaller and lighter, and more efficient. This technology is increasingly being improved, as all tests show that materials thus converted to nanoscale are more efficient in their performance.